Impact of COVID-19 outbreak on mental health and perceived strain among caregivers tending children with special needs - Dhiman, Sapna (Res Dev Disabil, 2020)
BACKGROUND: While COVID-19 outbreak has had adverse psychological effects in children with special needs, the mental state and burden on their caregivers during this pandemic has yet to be reported. AIMS: The objectives of this study were to describe the mental health status and the change in perceived strain among caregivers during the COVID-19 outbreak. METHODS AND PROCEDURES: Two hundred sixty four caregivers completed an online survey that assessed demographics, use and perspective on tele-rehabilitation, homecare therapy, caregiver’s strain and mental health. OUTCOMES AND RESULTS: The prevalence of depression, anxiety and stress symptoms were found to be 62.5 %, 20.5 % and 36.4 % respectively. A significant difference in caregiver strain (p <  0.001, effect size = 0.93) was observed during the outbreak compared to levels pre-outbreak (pre-outbreak strain was measured retrospectively). Caregivers not using tele-rehabilitation along with a perception of it being a poor medium for rehabilitation were at greater risks for poor mental health whereas a negative perception on homecare therapy were strongly associated with higher psychological symptoms and strain. CONCLUSIONS AND IMPLICATIONS: This study identified a high prevalence of depression and significant change in strain displayed by caregivers during the COVID-19 outbreak. We identified several factors associated with poor mental health and perceived strain that can be used to help safeguard caregivers.